2017
DOI: 10.1136/bmj.j373
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of primary care matters and should be protected

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…These findings are consistent with previous studies that found relational continuity to be associated with reduced risk of ACSC admission in a range of different patient groups . Higher continuity of family physician care may reduce the need for hospital care through improved management of physical health, by facilitating familiarity, communication, trust, and quality of relationship between doctor and patient . The results also suggest that the documentation and sharing of information and management plans across physicians within a family practice can have important benefits for both the physical and mental health of people with SMI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with previous studies that found relational continuity to be associated with reduced risk of ACSC admission in a range of different patient groups . Higher continuity of family physician care may reduce the need for hospital care through improved management of physical health, by facilitating familiarity, communication, trust, and quality of relationship between doctor and patient . The results also suggest that the documentation and sharing of information and management plans across physicians within a family practice can have important benefits for both the physical and mental health of people with SMI.…”
Section: Discussionsupporting
confidence: 90%
“…It is valued by patients 9,10 and providers 11 and considered good practice in mental health and family medicine, [12][13][14] reducing fragmentation of care and facilitating better provider-patient relationships. 15 Relational continuity-the longitudinal relationship between a patient and a health care practitioner (or group of practitioners) 16 -is often the focus of efforts to improve continuity. To date, evidence has been mixed on whether relational continuity improves outcomes for people with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…This finding might be highly relevant for policy makers because of increasing size of elderly populations. 37 Discontinuity of care reduces the opportunity for building trust and mutual responsibility between patients and physicians, which might underlie the increased risk of emergency hospital admission. 37 More qualitative and quantitative research is needed, therefore, to understand the relationship between continuity of care and reasons for admission, and to understand patients' values and experiences of continuity of care.…”
Section: Implications For General Practices and Future Researchmentioning
confidence: 99%
“…37 Discontinuity of care reduces the opportunity for building trust and mutual responsibility between patients and physicians, which might underlie the increased risk of emergency hospital admission. 37 More qualitative and quantitative research is needed, therefore, to understand the relationship between continuity of care and reasons for admission, and to understand patients' values and experiences of continuity of care. 38 Distinguishing between general practitioner-referred emergency hospital admissions and admissions through an emergency department requires a larger data set.…”
Section: Implications For General Practices and Future Researchmentioning
confidence: 99%
“…In a linked editorial,2 researchers at the University of Bristol suggested that seeing the same doctor “builds trust and a sense of mutual responsibility between patients and GPs,” while a primary care system that is increasingly fragmented “provides the setting for patients to choose to attend an emergency department instead.”…”
mentioning
confidence: 99%